Organized Crime and Drug Trafficking in Italy (Kriminalističke teme, 2019)
Reason for writing and research problem(s): In the global drug market Italy is both a destination and a transit country. Although the main position within the drug market in Italy have the local mafias, foreign criminal organizations play an important role at all levels of the drug chain across Italy. Among the foreign actors involved in the drug trafficking there are criminal groups from the Balkans. Their relationships with local criminal organizations shows to occupy a great slide of criminal markets by merging economic and cultural elements, thereby posing significant challenges to law enforcement agencies in terms of investigations, and also to scholars in terms of theoretical understanding.Aims of the paper (scientific and/or social): The aim of this paper is to explore the characteristics of organized criminal groups operating in drug business in Italy.Methodology/ Design: Data on drug related organized crime in Italy will be presented through analysis of findings revealed by investigation of two criminal operations (Loptice and Elefante Bianco) presenting the most common characteristics of Western Balkan groups and Albanian groups respectively. In order to collect the data, interviews with law enforcement officers were carried out.Results/ Findings: Although the legislative and investigative instruments, developed in the last forty years, have been proved to be very effective against the criminal activities carried out by organized crime, the national mafias and foreign criminal associations keep challenging Italian society. The experience acquired in the fight against the Sicilian mafia suggests to face these complex forms of criminality not only from a penal perspective, but also from a socio-economic and cultural one.